Effectiveness of guideline preoperative induction checklist in Songklanagarind Hospital - Benjhawaleemas, Pannawit; Dilokrattanaphichit, Nussara; Juthasantikul, Wipharat; Phakam, Pannipa; Oofuvong, Maliwan (Thai Journal of Anesthesiology, 2022)
Background: The preoperative induction checklist (I AM SAM) to be the part of the patient safety hospital has been developed at our anesthesiology department. Objectives: The research team investigated the anesthesia related adverse events after using I AM SAM checklist. Methods: This prospective observational study including patients who received anesthesia from January 2019-July 2020. The anesthesia team (anesthesiologist/nurse anesthetist) performed I AM SAM checklist before, during and after induction of anesthesia as well as recorded information regarding adverse events in the record form until completing the surgery. The descriptive statistics were described by frequency and percentage Results: A total of 1,855 patients were recruited. The completion of the checklist was almost 100% of each item. After using I AM SAM checklist, the incidence of intravenous leakage was found the most (0.92%), the second most incidence was medication error (0.49%), the third most incidence was equipment failure (0.27%), and incidence of cardiac arrest and hypoxemia were 0.22%. No incidence of failed intubation, Transfusion mismatch and wrong patient wrong site were found in this study. Conclusions: The completion of the checklist I AM SAM was almost 100% of each item. The two most incidence found after using I AM SAM checklist were intravenous leakage and medication error, respectively.